2007
DOI: 10.1016/j.jcrs.2007.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the corneal epithelium to anterior corneal topography in patients having myopic photorefractive keratectomy

Abstract: The epithelium affected the topographic properties of the cornea by significantly reducing corneal topographic astigmatism and irregularity. This might prove to be important in the assessment of patient candidacy for and treatment planning in refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
1
37
2
Order By: Relevance
“…This led to a normal post-refractive surgery topography ( Figure 5, right), which is consistent with the finding of Gatinel et al, 9 showing that the epithelium has the ability to significantly modify the curvature, elevation, and asphericity of corneal topography maps. The uniformity in aberrometry can also be explained by the surface-smoothing effect of the epithelium, as well as the lower sampling resolution compared with topography.…”
Section: Beneficial Refractive Effect Of the Epitheliumsupporting
confidence: 90%
“…This led to a normal post-refractive surgery topography ( Figure 5, right), which is consistent with the finding of Gatinel et al, 9 showing that the epithelium has the ability to significantly modify the curvature, elevation, and asphericity of corneal topography maps. The uniformity in aberrometry can also be explained by the surface-smoothing effect of the epithelium, as well as the lower sampling resolution compared with topography.…”
Section: Beneficial Refractive Effect Of the Epitheliumsupporting
confidence: 90%
“…Recently, we studied the effect of removal of the corneal epithelium on corneal videotopography. 27 By performing Orbscan IIz slit-scanning corneal topography before and just after corneal deepithelialization (before photoablation delivery) in myopic patients during photorefractive keratectomy, we found significant topographic differences between the air-tear film interface and Bowman layer. In particular, increased prolateness, irregularity, and toricity were seen after simple corneal epithelial debridement.…”
Section: Discussionmentioning
confidence: 80%
“…Irregularity indices, asphericity, and K readings increased consistently in almost all eyes, confirming that the stromal bulge caused by the ectasia was significantly reduced by the epithelium. Gatinel et al 16 also found that normal corneas had a more prolate shape after epithelial removal. In their study, the mean central power was 44.42 G 1.59 (SD) for epi-on and 43.46 G 1.37 for epi-off (delta epi-on À epi-off Z 0.96 D); the mean Q value was À0.44 G 0.14 and À0.65 G 0.46, respectively (delta epi-on À epi-off Z À0.21 D); and the average simulated K was 43.77 G 1.83 and 42.44 G 1.73, respectively (delta epi-on À epi-off Z 1.33 D).…”
Section: Discussionmentioning
confidence: 93%
“…In 2007, Gatinel et al 16 were the first to suggest performing topographic analyses after epithelial removal. Using an Orbscan II topography system (Bausch & Lomb), they studied 44 normal eyes treated with PRK for myopia.…”
Section: Discussionmentioning
confidence: 99%